A Cross - Sectional Descriptive Study of Relation of Clotting Time and Mizaj in Young Adults. - Hashmi, Iqra; Jamal, Yusuf (International Research Journal of Ayurveda & Yoga, 2022)
Background-Concept of mizaj in the Unani system of medicine is a wide area of research. Mizaj is the main thing that confers a legitimate shape and construction to the human body and makes an individual skilled to appropriately carry out his functions. In the event that the Mizaj of an individual is changed, his capabilities, as well as designs, will generally change, bringing about diseases. Any demeanour of a sound individual addresses a decent profile of the normal state which keeps ideal concordance between the milieu Interieur (the environment inside the body) and the environment outside. Therefore, it is important to understand its link to physiology of clotting time, which may be influenced by individual mizaj (body type). So, it is necessary to find out its relationship with clotting time which may be influenced by individual mizaj (body type) and it can be considered as a decisive advantage to selecting an appropriate diagnostic tool for treatment in clinical practice. Research in this area is very scanty and inconclusive, therefore the participants of young age and clinically healthy have been chosen as the subject of study. Objective(s)- The objective of the present study is to find out the nature of mizaj (body type) with clotting time. Material and Methods- Using simple random sampling in Delhi (India) Sixty-two (62) college students from Ayurvedic and Unani Tibbia college and Hospital, Karol Bagh were selected as per inclusion and exclusion criteria and asked to complete the Mizaj questionnaire followed by checking of clotting time of each paticipants face to face under supervison. SPSS statistics software 22.0 was used for was used to establish a database for statistical description. The One-way ANOVA test in SPSS was used to analyze the differences between the groups. P < 0.05 suggested that the difference was statistically significant. Results- Based on the results it is found that clotting time is lowest in people having Damvi Mizaj and safravi Mizaj and highest in balghami and saudavi mizaj which is in concordance with the experimental hypothesis of this research work. Conclusion- From this study, it is clear that a possible correlation between clotting time (CT) and Mizaj certainly does exist. After that, clotting time could be considered as one of the diagnostic indices of temperament.